Preparation method of ethynyl-nitrogen phosphorus benzoxazine-containing resin for copper-clad plate
By introducing ethynyl-containing and nitrogen-phosphorus-based structures into the copper clad resin and combining vanillin-free flame retardant, the shortcomings of existing resins in heat resistance and flame retardant properties are solved, and higher heat resistance and flame retardant properties are achieved, and the performance of copper clad plates is optimized.
Patent Information
- Application Number
- CN202411886785.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing copper clad resins have shortcomings in process preparation, heat resistance and flame retardant properties. In particular, the glass transition temperature of common bifunctional benzoxazine resins is usually between 160-200°C, which is difficult to meet the heat resistance requirements above 250°C.
The preparation method of ethynyl-nitrogen phosphobenzoxazine resin is adopted to improve the heat resistance and flame retardant of the resin by introducing N elements and combining vanillin-free halogen-free flame retardant, and the phosphorus-containing halogen-free flame retardant is synthesized through addition reactions, which significantly improves the performance of the resin.
It significantly improves the heat resistance and flame retardancy of the resin, exhibits higher residual carbon content and excellent carbon layer continuity and density, effectively optimizing the performance of the final product.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a polymer material, in particular to a method for preparing an acetylene-nitrogen-phosphorus benzoxazine resin for copper-clad laminates. Background Art
[0002] Copper-clad laminates (CCLs), a foundational material for electronic components, are widely used in electronics, medical, aerospace, and other fields. They are made from fiberglass impregnated with a resin adhesive, dried, coated with copper foil, and finally processed in a hot press under high temperature and high pressure. Phenolic and epoxy resins are commonly used in the industry to prepare resin adhesives, but these various resins have drawbacks in terms of process preparation, heat resistance, and flame retardancy.
[0003] Benzoxazine resin, a new type of thermosetting resin that has matured over the past 40 years, is a special type of phenolic resin. It offers numerous advantages, including simple molding and polymerization conditions, low melt viscosity, near-zero volume expansion and contraction during polymerization, and exceptional molecular designability. By selecting raw materials containing specific functional groups, benzoxazine resins can be synthesized to meet specific application requirements. Compared to traditional phenolic resins, benzoxazine resins not only retain their advantages but also address a significant number of their shortcomings. As a base resin for copper-clad laminates, benzoxazine resins require high heat resistance, with a glass transition temperature (Tg) exceeding 250°C. However, the glass transition temperatures of common difunctional benzoxazine resins typically range from 160°C to 200°C, creating a pressing need for improved performance. Summary of the Invention
[0004] The present invention provides a method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for copper-clad laminates. This method incorporates nitrogen into the components and combines them with a vanillin-based halogen-free flame retardant. The resulting system significantly improves heat resistance and flame retardancy, exhibits a higher carbon residue, and exhibits excellent carbon layer continuity and density, effectively optimizing the performance of the final product.
[0005] The purpose of the present invention is achieved through the following technical solutions: A method for preparing an acetylene-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate, the method comprising the following steps: a. Preparation of a phosphorus-containing halogen-free flame retardant: Vanillin (3-methoxy-4-hydroxybenzaldehyde) and 2-aminobenzimidazole are mixed in a molar ratio of 1:1, and placed in a three-necked flask equipped with a magnetic stirring rotor together with a solvent and an alkaline solution and mixed evenly; the reaction temperature of the system is controlled at 50-70°C, and stirring is continued at this temperature for 7-10 hours; then, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide solution is added to the system, the system temperature is maintained constant, nitrogen is introduced, and stirring is continued for 7-10 hours under the protection of nitrogen; after the reaction is completed, the product is subjected to rotary evaporation to obtain a white viscous latex liquid, which is then slowly poured into anhydrous ethanol to ensure that the solution is fully mixed; then, the mixed solution is placed in a beaker for recrystallization; after the recrystallization is completed, vacuum filtration is performed, and deionized water is used for three times for full purification; then the product is placed in an oven at 70°C to dry to constant weight to obtain a yellow powder; b. Preparation of acetylene-containing benzoxazine resin: 3-aminophenylacetylene and aniline were mixed in a reaction flask, and then an aldehyde was added. The reaction system was reacted at 40°C for 1 hour. After the reaction was completed, a phenol was added to dissolve the phenol, and the temperature was raised to 120°C and stirred until the system became transparent. The acetylene-containing benzoxazine resin was then dried in an oven at 70°C to obtain the acetylene-containing benzoxazine resin.
[0006] In the method for preparing an acetylene-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate, the alkaline solvent comprises one or more of pyridine, imidazole, triethylamine, sodium ethoxide, sodium methoxide, diethylamine, potassium hydroxide, sodium hydroxide, and potassium tert-butoxide.
[0007] The method for preparing an acetylene-nitrogen phosphorus benzoxazine resin for a copper clad laminate, wherein the organic solvent comprises one of methanol, acetonitrile, ethanol, cyclopentanone, dichloromethane, chloroform, carbon tetrachloride, tetrahydrofuran, hexamethylphosphoramide, dimethylacetamide, and N-methylpyrrolidone.
[0008] In the method for preparing an acetylene-nitrogen-phosphorus benzoxazine resin for copper-clad laminates, the molar ratio of 3-aminophenylacetylene to aniline is 0.9:1.
[0009] In the method for preparing an acetylene-nitrogen-phosphorus benzoxazine resin for copper-clad laminates, the phenolic substance is phenol, bisphenol A, or bisphenol F.
[0010] In the method for preparing an acetylene-nitrogen-phosphorus benzoxazine resin for copper-clad laminates, the aldehyde substance is one of paraformaldehyde and formaldehyde aqueous solution.
[0011] In the method for preparing an acetylene-nitrogen-phosphorus benzoxazine resin for copper-clad laminates, the molar ratio of the paraformaldehyde to the phenol source is 4:1.
[0012] The beneficial effects of the present invention are: The invention firstly uses 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to carry out addition reaction with vanillin to synthesize a phosphorus-containing halogen-free flame retardant. The preparation process is convenient and simple, and the yield is high.
[0013] The incorporation of acetylene groups into the benzoxazine ring significantly improves the heat resistance of benzoxazine.
[0014] The cross-linking density of the curing system with acetylene-containing benzoxazine resin as the curing agent is significantly improved, and it also has a higher residual carbon content and better continuous and dense carbon layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the molecular formula of the phosphorus-containing halogen-free flame retardant of the present invention; Figure 2 is the reaction equation of the acetylene-containing benzoxazine resin of the present invention. DETAILED DESCRIPTION
[0016] The present invention is further described below with reference to the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. However, the embodiments are not intended to limit the present invention. Example 1
[0017] Preparation of phosphorus-containing halogen-free flame retardant 15.2 g (0.1 mol) of vanillin and 13.3 g (0.1 mol) of 2-aminobenzimidazole were mixed with methanol and triethylamine solution in a three-necked flask equipped with a magnetic stirring rotor and mixed thoroughly. The reaction temperature was controlled at 50-70°C and stirred continuously at this temperature for 7-10 hours. A solution of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was then added. The system temperature was maintained constant while nitrogen was purged and stirred continuously for 7-10 hours under nitrogen protection. After the reaction was completed, the product was rotary evaporated to obtain a white, viscous latex-like liquid. This liquid was then slowly poured into anhydrous ethanol to ensure thorough mixing. The mixed solution was then recrystallized in a beaker. After recrystallization, the mixture was vacuum filtered and washed three times with deionized water to ensure complete purification. The product was then dried in an oven at 70°C to constant weight to obtain a phosphorus-containing, halogen-free flame retardant.
[0018] (2) Preparation of ethynyl-containing benzoxazine resin Add 25.2 g (0.9 mol) of paraformaldehyde and a mixture of 37.2 g of aniline and 3-ethynylaniline (0.4 mol) to a reaction flask, mix well, heat to 40°C, and react for 1 hour. Add 57 g of bisphenol A (0.25 mol), heat the reaction system to 110°C, and react for 0.5 hour. Pour the solution out while it is clear and cool to room temperature to obtain an ethynyl-containing benzoxazine resin. Example 2
[0019] (1) Preparation of phosphorus-containing halogen-free flame retardants 7.6 g (0.05 mol) of vanillin and 6.65 g (0.05 mol) of 2-aminobenzimidazole were mixed with dichloromethane and aqueous sodium hydroxide in a three-necked flask equipped with a magnetic stirring rotor and mixed thoroughly. The reaction temperature was controlled at 50-70°C and stirred continuously for 7-10 hours. A solution of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was then added. The system temperature was maintained constant while nitrogen was introduced and stirring was continued for 7-10 hours under nitrogen protection. After the reaction was complete, the product was rotary evaporated to obtain a white, viscous latex-like liquid. This liquid was then slowly poured into anhydrous ethanol to ensure thorough mixing. The mixed solution was then recrystallized in a beaker. After recrystallization, it was vacuum filtered and washed three times with deionized water to ensure complete purification. The product was then dried in an oven at 70°C to constant weight to obtain a phosphorus-containing, halogen-free flame retardant.
[0020] (2) Preparation of ethynyl-containing benzoxazine resin Add 1.23 g (0.04 mol) of paraformaldehyde and 2.34 g (0.02 mol) of 3-ethynylaniline to a reaction flask, mix well, heat to 40°C, and react for 1 hour. Add 2.002 g (0.01 mol) of bisphenol F, heat the reaction system to 110°C, and react for 0.5 hour. Pour the mixture hot when it becomes clear, and cool to room temperature to obtain an ethynyl-containing benzoxazine resin. Example 3
[0021] (1) Preparation of phosphorus-containing halogen-free flame retardants 7.6 g (0.05 mol) of vanillin and 6.65 g (0.05 mol) of 2-aminobenzimidazole were mixed with dimethylacetamide and potassium tert-butoxide solution in a three-necked flask equipped with a magnetic stirring rotor and mixed thoroughly. The reaction temperature was controlled at 50-70°C and stirred continuously for 7-10 hours. A solution of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was then added. The system temperature was maintained constant while nitrogen was purged and stirred continuously for 7-10 hours under nitrogen protection. After the reaction was completed, the product was rotary evaporated to obtain a white, viscous latex. This liquid was then slowly poured into anhydrous ethanol to ensure thorough mixing. The mixed solution was then recrystallized in a beaker. After recrystallization, the mixture was vacuum filtered and washed three times with deionized water to ensure complete purification. The product was then dried in an oven at 70°C to constant weight to obtain a phosphorus-containing, halogen-free flame retardant.
[0022] (2) Preparation of ethynyl-containing benzoxazine resin Add 1.23 g (0.04 mol) of paraformaldehyde and 1.86 g (0.02 mol) of aniline to a reaction flask, mix well, heat to 40°C, and react for 1 hour. Add 1.88 g (0.02 mol) of phenol, heat the reaction system to 110°C, and react for 0.5 hour. Pour out the mixture while it becomes transparent and cool to room temperature to obtain an ethynyl-containing benzoxazine resin. Example 4
[0023] (1) Preparation of phosphorus-containing halogen-free flame retardants 3.04 g (0.02 mol) of vanillin and 2.66 g (0.02 mol) of 2-aminobenzimidazole were mixed with ethanol and triethylamine in a three-necked flask equipped with a magnetic stirring rotor and mixed thoroughly. The reaction temperature was controlled at 50-70°C and stirred continuously for 7-10 hours. A solution of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was then added. The system temperature was maintained constant while nitrogen was purged and stirred continuously for 7-10 hours under nitrogen protection. After the reaction was completed, the product was rotary evaporated to obtain a white, viscous latex-like liquid. This liquid was then slowly poured into anhydrous ethanol to ensure thorough mixing. The mixed solution was then recrystallized in a beaker. After recrystallization, the mixture was vacuum filtered and washed three times with deionized water to ensure complete purification. The product was then dried in an oven at 70°C to constant weight to obtain a phosphorus-containing, halogen-free flame retardant.
[0024] (2) Preparation of ethynyl-containing benzoxazine resin 1.23 g (0.04 mol) of paraformaldehyde, 0.93 g of aniline (0.01 mol), and 1.17 g of 3-ethynylaniline (0.01 mol) were added to a reaction flask, mixed evenly, heated to 40°C, and reacted for 1 hour. 2.002 g (0.01 mol) of bisphenol F was added, and the reaction system was heated to 110°C and reacted for 0.5 hour. When the system became transparent, the mixture was poured out while hot and cooled to room temperature to obtain an ethynyl-containing benzoxazine resin. Example 5
[0025] (1) Preparation of phosphorus-containing halogen-free flame retardants 15.2 g (0.1 mol) of vanillin and 13.3 g (0.1 mol) of 2-aminobenzimidazole were mixed, along with ethanol and an appropriate amount of imidazole, in a three-necked flask equipped with a magnetic stirring rotor and mixed thoroughly. The reaction temperature was controlled at 50-70°C and stirred continuously for 7-10 hours. A solution of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was then added. The system temperature was maintained constant while nitrogen was purged and stirred continuously for 7-10 hours under nitrogen protection. After the reaction was complete, the product was rotary evaporated to obtain a white, viscous latex-like liquid. This liquid was then slowly poured into anhydrous ethanol to ensure thorough mixing. The mixed solution was then recrystallized in a beaker. After recrystallization, the mixture was vacuum filtered and washed three times with deionized water to ensure complete purification. The product was then dried in an oven at 70°C to constant weight to obtain a phosphorus-containing, halogen-free flame retardant.
[0026] (2) Preparation of ethynyl-containing benzoxazine resin 6.06 g (0.2 mol) of paraformaldehyde, 3.73 g of aniline (0.04 mol), and 7.03 g of 3-ethynylaniline (0.06 mol) were added to a reaction flask, mixed evenly, heated to 40°C, and reacted for 1 hour. 10 g (0.05 mol) of bisphenol F was added, and the reaction system was heated to 110°C and reacted for 0.5 hour. The system was poured out while transparent and cooled to room temperature to obtain an ethynyl-containing benzoxazine resin.
[0027] The benzoxazine resin curing agents obtained in the above examples and comparative examples were respectively mixed with 9% vanillin phosphorus-containing halogen-free flame retardant and epoxy resin using a solvent, and a curing accelerator, 2-phenylimidazole, was added. After the curing reaction, the limiting oxygen index (LOI) and vertical burning UL-94 tests were performed. The test results are shown in Table 1.
[0028] Table 1 Test results of examples and comparative examples
[0029] The limiting oxygen index in Table 1 was determined according to the national standard method GB / T 2406.2-2009, and the UL-94 vertical burning test adopted the standard GB / T 2408-2008.
Claims
1. A method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate, characterized in that: The method comprises the following steps: a. Preparation of phosphorus-containing halogen-free flame retardant: vanillin (3-methoxy-4-hydroxybenzaldehyde) and 2-aminobenzimidazole are mixed in a molar ratio of 1:1, and placed in a three-necked flask equipped with a magnetic stirring rotor together with a solvent and an alkaline solution to mix evenly; the reaction temperature of the system is controlled at 50-70°C, and stirring is continued at this temperature for 7-10 hours; then 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide solution is added to the system, the system temperature is kept constant and nitrogen is introduced, and stirring is continued for 7-10 hours under the protection of nitrogen; after the reaction is completed, the product is subjected to rotary evaporation to obtain a white viscous latex liquid, and then the liquid is slowly poured into anhydrous ethanol to ensure that the solution is fully mixed; then, the mixed solution is placed in a beaker for recrystallization; after the recrystallization is completed, vacuum filtration is performed, and deionized water is used for washing three times to fully purify; then the product is placed in an oven at 70°C to dry to constant weight to obtain a yellow powder; b. Preparation of acetylene-containing benzoxazine resin: 3-aminophenylacetylene and aniline were mixed evenly in a reaction bottle, and then aldehydes were added. The reaction system was reacted at 40°C for 1 hour. After the reaction was completed, phenols were added to dissolve and then the temperature was raised to 120°C and stirred until the system was transparent; then the acetylene-containing benzoxazine resin was obtained by drying in an oven at 70°C.
2. The method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate according to claim 1, characterized in that: The alkaline solvent includes one or more of pyridine, imidazole, triethylamine, sodium ethoxide, sodium methoxide, diethylamine, potassium hydroxide, sodium hydroxide and potassium tert-butoxide.
3. The method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate according to claim 1, characterized in that: The organic solvent includes one of methanol, acetonitrile, ethanol, cyclopentanone, dichloromethane, chloroform, carbon tetrachloride, tetrahydrofuran, hexamethylphosphoric triamide, dimethylacetamide, and N-methylpyrrolidone.
4. The method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate according to claim 1, characterized in that: The molar ratio of 3-aminophenylacetylene to aniline is 0.9:
1.
5. The method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate according to claim 1, characterized in that: The phenolic substances are phenol, bisphenol A and bisphenol F.
6. The method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate according to claim 1, characterized in that: The aldehyde substance is one of paraformaldehyde and formaldehyde aqueous solution.
7. The method for preparing an ethynyl-nitrogen-phosphorus benzoxazine resin for a copper-clad laminate according to claim 1, characterized in that: The molar ratio of the paraformaldehyde to the phenol source is 4:1.
Citation Information
Patent Citations
Benzoxazine resin, preparation method thereof and impregnating adhesive for halogen-free phosphorus-free flame retardant copper-clad plate fabricated by taking the benzoxazine resin as raw material
CN102408419A
Reversible thermosensitive recording material
JP2012196856A